Dampak Pandemi Terhadap Pelaporan Realisasi Anggaran Pada Sekretariat Utama Kementerian Pariwisata Dan Ekonomi Kreatif - Trisha Aisyah Kusumajati; Puji Wibowo (PT Wim Solusi Prima, 2022)
The main secretariat of the Ministry of Tourism and Creative Economy as part of the government of the republic of Indonesia must be able to apply all applicable government standards or regulations. Since the beginning of 2020, the pandemic of Covid-19 has hit and forced the central government to issue policies related to budget treatment and expenditure realization for all ministries and institutions in Indonesia. Responding to the policy, the main secretariat of the Ministry of Tourism and Creative Economy began the best possible adjustments. In this study, the authors conducted interviews as primary data and examined the unaudited financial statements belonging to the main secretariat of the Ministry of Tourism and Creative Economy in 2020 as secondary data. With these two data, it can be seen what and how adjustments have been made during a period of 1 year. The main secretariat of the Ministry of Tourism and Creative Economy seems to have implemented the policy very well, all aspects that have become the author's assessment have been properly implemented by the main secretariat of the Ministry of Tourism and Creative Economy, including one of the important points, namely the refocusing of activities and budget reallocation, which also looks very significant and on target. Sekretariat Utama Kementerian Pariwisata dan Ekonomi Kreatif sebagai bagian dari Pemerintah Republik Indonesia harus mampu menerapkan semua standar atau peraturan pemerintah yang berlaku. Sejak awal tahun 2020, pandemi Covid-19 melanda dan memaksa pemerintah pusat mengeluarkan kebijakan terkait penanganan anggaran dan realisasi belanja untuk seluruh kementerian dan lembaga di Indonesia. Menyikapi kebijakan tersebut, Sekretariat Utama Kementerian Pariwisata dan Ekonomi Kreatif mulai melakukan penyesuaian sebaik mungkin. Dalam penelitian ini, penulis melakukan wawancara sebagai data primer dan meneliti laporan keuangan unaudited milik sekretariat utama Kementerian Pariwisata dan Ekonomi Kreatif tahun 2020 sebagai data sekunder. Dengan kedua data tersebut dapat diketahui apa dan bagaimana penyesuaian yang telah dilakukan selama kurun waktu 1 tahun. Sekretariat utama Kementerian Pariwisata dan Ekonomi Kreatif tampaknya telah menerapkan kebijakan dengan sangat baik, semua aspek yang menjadi penilaian penulis telah dilaksanakan dengan baik oleh sekretariat utama Kementerian Pariwisata dan Ekonomi Kreatif, termasuk salah satu yang penting. poin yaitu refocusing kegiatan dan realokasi anggaran yang juga terlihat sangat signifikan dan tepat sasaran.